Neuroenhancement and the strength model of self-control - Englert, Chris; Wolff, Wanja (Frontiers in Psychology, 2015)
Neuroenhancement (NE), the use of substances as a means to enhance performance, has garnered considerable scientific attention of late. While ethical and epidemiological publications on the topic accumulate, there is a lack of theory-driven psychological research that aims at understanding psychological drivers of NE. In this perspective article we argue that self-control strength offers a promising theory-based approach to further understand and investigate NE behavior. Using the strength model of self-control, we will derive two theory-driven perspectives on NE-self-control research. First, we propose that individual differences in state/trait self-control strength differentially affect NE behavior based on one’s individual experience of NE use. Building upon this, we will outline promising research questions that will further elucidate our understanding of NE based on the strength models propositions. Second, we will discuss evidence indicating that popular NE substances (like Methylphenidate) might counteract imminent losses of self-control strength. We will outline how further research on NE’s effects on the ego-depletion effect might further broaden our understanding of the strength model of self-control.